Community health workers’ knowledge of Ubuntu informed care in tuberculosis, HIV, and AIDS in Gauteng province - Rodwell Gundo; Nombulelo V. Sepeng; Robert Lavhelani; Mabitja Moeta; Maurine Musie; Raikane J. Seretlo; Fhumulani M. Mulaudzi (Curationis, 2025)
Background: Community health workers (CHWs) work with community members who experience various health problems. They assist community members to lead a healthy life and achieve an acceptable health status. To achieve this, there is a need for CHWs to apply Ubuntu philosophy when providing care related tuberculosis (TB), Human Immunodeficiency Virus (HIV), and acquired immunodeficiency syndrome (AIDS).